Las respuestas lectoras en niños preadolescentes: Espejo de la agresión - Raquel C. Cuperman (Universitat Autònoma de Barcelona, 2010)
This study used picture books from the field of literature for children and young people to detect the roles of bully and victim taken on by adolescents in a school of high socioeconomic status in Bogotá, Colombia. Readers' responses arising from literary discussions pointed to conflicts of social inequality and intolerance. These were cross-checked with a questionnaire on television preferences; a questionnaire on identification with bullies and victims in TV series; notes taken by the observer of the school's pupils; a questionnaire on the frequency of bullying suffered and carried out.